The Use of Flashcard Media to Improve Arabic Vocabulary Mastery of Fifth Grade Students at MI Tiwu Lekong - Muhamad Hasyim (Formad English Foundation NTB-Jakarta, 2025)
This study aimed to improve Arabic vocabulary (mufradat) mastery among fifth-grade students at MI Tiwu Lekong through the implementation of flashcard media. The study was motivated by the problem of low vocabulary mastery, retention, and student engagement in Arabic lessons, which stemmed from the dominance of traditional lecture-based instruction and the absence of interactive visual aids. This research employed a Classroom Action Research (CAR) approach based on Lewin’s model, which consists of planning, action, observation, and reflection, conducted over two instructional cycles. The sample comprised 25 students, and data were collected through observation, interviews, performance assessments, and documentation. Findings revealed a progressive improvement in students' vocabulary mastery. In the pre-cycle phase, only 44% of students met the Minimum Mastery Criteria (MMC). After the first cycle, 64% of students showed improved performance, and by the second cycle, the mastery level increased to 88%, with 28% of students achieving an “Excellent” classification. The use of flashcards not only enhanced vocabulary retention but also stimulated student motivation and participation. The results suggest that flashcard media is an effective pedagogical tool for Arabic vocabulary acquisition in elementary settings. It supports both receptive and productive language skills and aligns with young learners’ cognitive styles. This study provides practical insights for Arabic language teachers, especially in rural schools, and recommends further exploration of low-cost, interactive media in language instruction.